Removal of Iron from Groundwater by Ozonation: The Response Surface Methodology for Parameter Optimization: 10.32526/ennrj/19/2020286 - Sukmilin, Apiradee; Sangsirimongkolying, Ratsamee (Environment and Natural Resources Journal, 2021)
This research studied the possibility of using ozone to remove iron from groundwater. The optimum conditions were investigated using a Box-Behnken experiment design with statistical analysis by response surface technique. The three parameters investigated, pH (6.0-8.0), hardness (300-500 mg/L as CaCO3) and removal time (10 to 60 min) were independent parameters of iron removal. Data was examined for optimal conditions and included main effects and their interactions. Analysis of variance indicated that the proposed quadratic model successfully interpreted the experimental data with a coefficient of determination (R2) of 98.83% and adjusted R2 of 96.72%. Through this model, it could predict the iron removal efficiency under variable conditions. Furthermore, the optimum conditions were pH 6.99, hardness of 300 mg/L as CaCO3, and 10 min of reaction time. The predicted iron removal efficiency obtained from the model under the optimum conditions was 99.00%. The experiment confirmed that the optimum condition which validated the model’s accuracy of iron removal efficiency was 98.45%. The results showed that ozone can remove iron from groundwater.